The concept of a health security system model during a pandemic - Szymonik Artur (2022)
The necessity of proper health security management is determined by its decisive role in ensuring survival conditions. Estimating the risk in the area of health security and striving to implement appropriate models of the health security system seems to be crucial in the process of managing it. Effective healthcare management is one of the key elements of a healthier society, where positive action in the identified area of research, technology and management has great potential to improve the global response to potential future health crises. The aim of this study is to propose a model of the health security system, taking into account the dynamics of changes in its determinants caused by the COVID - 19 pandemic. The intention of the presented solutions is to optimize the use of available resources during the health crisis. The main research problem of the article is the question: how would the new model of the health security system take into account the needs of health care in the conditions of the COVID - 19 pandemic? Using the observational method, available research as well as exploratory and intervention data related to COVID-19, an attempt was made to propose a model aimed at efficient management of medical care provided to patients. Not only patients with COVID - 19 but also with other diseases, and healthy people, as part of integrated framework for broadly understood prevention. Focusing on technology-oriented models together with a well-matched infrastructure may result in better results in the prevention and care of COVID - 19 patients. The aforementioned technological development will also serve the implementation of new models enabling the application of genomics, proteomics, nanotechnology, materials science and digital devices for early diagnosis and infection control. The presented model has been developed taking into account various factors and conditions that may affect its efficiency, as well as the proper functioning of the health security system.